Temporal analysis of the performance of an elevated concrete tank considering the corrosion of the steel reinforcement. - Nassima Miloudi; Karima Bouzelha; Hocine Hammoum; Younes Aoues; Ouali Amiri (Fracture and Structural Integrity)
Reinforced concrete water storage tanks are civil engineering structures subject to very aggressive atmospheric conditions that expose them to harmful corrosion risk. This dangerous phenomenon caused by the penetration of chloride ions causes pitting corrosion and leads to the reduction of the section of the reinforcements and consequently to the loss of strength and the structure performance. In this study, we are interested in analyzing the performance of an elevated storage tank, taking into account the corrosion of the reinforcements subjected to tensile stress, by considering environments with different rates of aggressiveness. A method based on Housner's model is used to evaluate the tension stresses in the reinforced concrete (RC) pedestal (supporting system) of the tank, subjected to the seismic actions. A pitting corrosion model is developed in order to determine the evolution in time of the reinforcements section in different environments. Several parameters influencing corrosion are taken into account, such as concrete cover and the concentration of chlorides ions.